2010
DOI: 10.1001/archdermatol.2010.324
|View full text |Cite
|
Sign up to set email alerts
|

Early White Discoloration of Infantile Hemangioma

Abstract: To evaluate the relationship between early white discoloration of infantile hemangioma (IH) and ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…98 In such cases, early white discoloration of an IH, possibly representing superficial dermal fibrosis, may be a premonitory sign of impending ulceration. 99 Other proposed mechanisms include outgrowing of the blood supply or rapid expansion exceeding the elastic capabilities of the skin. 99,100 Several studies have shown that certain subsets of patients with IHs are at higher risk of ulceration.…”
Section: Ulcerationmentioning
confidence: 99%
See 1 more Smart Citation
“…98 In such cases, early white discoloration of an IH, possibly representing superficial dermal fibrosis, may be a premonitory sign of impending ulceration. 99 Other proposed mechanisms include outgrowing of the blood supply or rapid expansion exceeding the elastic capabilities of the skin. 99,100 Several studies have shown that certain subsets of patients with IHs are at higher risk of ulceration.…”
Section: Ulcerationmentioning
confidence: 99%
“…99 Other proposed mechanisms include outgrowing of the blood supply or rapid expansion exceeding the elastic capabilities of the skin. 99,100 Several studies have shown that certain subsets of patients with IHs are at higher risk of ulceration. As discussed previously, superficial and segmental IHs have been found to be at higher risk of ulcerating.…”
Section: Ulcerationmentioning
confidence: 99%
“…26.9 ). Early white discoloration (average age of 2.6 months) of HI is highly predictive of impending ulceration [ 38 ]. This sign should be differentiated from the typically centrifugal discoloration that heralds spontaneous or treatment-induced involution of HI and usually begins after the completion of tumor growth (Fig.…”
Section: Ulcerationmentioning
confidence: 99%
“…En un 80% de los casos, se observa un blanqueamiento temprano central en el HI antes de la ulceración. 51 Las comorbilidades producidas por la ulceración son múltiples e incluyen dolor, desfiguración, sobreinfección, anemia por sangrado, estrés paterno y secuelas cicatrizales. 6 El dolor puede preceder la aparición de la úlcera.…”
Section: Complicacionesunclassified
“…En la mayoría de los casos, el sangrado es mínimo y cesa ante la presión directa, pero puede ser muy alarmante para los padres. 12,[50][51][52][53] Existen localizaciones anatómicas que se asocian con mayor riesgo de disfunción vital,…”
Section: Complicacionesunclassified